Hormetic effects of galactose could be explained by rapid metabolic network disinhibition of the protective oxidative pentose phosphate pathway flux: Nonhuman/Lead optimization studies. (7th December 2020) - Homolak, Jan; Perhoc, Ana Babic; Knezovic, Ana; Barilar, Jelena Osmanovic; Salkovic‐Petrisic, Melita
Abstract: Background: Long‐term oral galactose treatment prevents and rescues cognitive deficits in rat model of Alzheimer's disease. In contrast, long‐term parenteral galactose treatment‐induced oxidative stress is used to model aging in rodents. The aim of this study was to provide new information on the effects of single acute oral galactose treatment, elucidate mechanisms responsible for both detrimental and protective effects, and explore their association with oxidative stress. Method: Male Wistar rats were acutely treated with D‐galactose (200mg/kg) by orogastric gavage and sacrificed 30, 60 or 120 minutes after the treatment. Oxidative stress, metabolic parameters and proteins of interest were analyzed by spectrophotometry, electrochemistry, western blotting, ELISA and novel method for spatiotemporal reductive analysis. Data was tested for normality and analyzed by exploratory factor analysis of mixed data. Most significant determinators of two primary components were identified and tested for group and intraexperimental differences by Wilcoxon test, intragroup and combined Pearson correlation coefficient. Result: Contribution analysis identified hippocampal NADP and NADPH, oxidative stress (superoxide dismutase (SOD) activity and redox couple oxidation‐reduction potential (rcORP)) and hippocampal expression of c‐fos and cytochrome c oxidase as primary determinants of the first component, and GLP‐1 total and active fractions as determinants of the second component. Acute oral galactose treatment increased hippocampal NADP, NADPH, cytochrome c oxidase, catalase activity and lipid peroxidation. Protein sulfhydryl content, SOD activity, and c‐fos were decreased by the treatment. Total amount of reduced glutathione and rcORP remained unchanged. Conclusion: Acute oral galactose treatment induced increase in oxidative stress markers with no effect on net tissue reductive potential suggests endogenous compensation of oxidative challenge. Rapid metabolic shift towards phosphorylation of nicotinamide adenine dinucleotides and decreased cellular activity points to oxidative pentose phosphate pathway disinhibition‐mediated activation of conserved protective reactive oxygen species detoxification mechanism as a potential mediator of galactose‐associated hormetic effects. This work was funded by the Croatian Science Foundation (IP‐2018‐01‐8938). Research was co‐financed by the Scientific Centre of Excellence for Basic, Clinical and Translational Neuroscience (project "Experimental and clinical research of hypoxic‐ischemic damage in perinatal and adult brain"; GA KK01.1.1.01.0007 funded by the European Union through the European Regional Development Fund).